Sotka Dam Seepage; Evaluation and Possible Remediation - Abdulrahman, Kawa Zeidan; Salih, Nihad Bahaaldeen; Ghafoor, Alan Abubaker (Sulaimani Journal for Engineering Sciences, 2016)
One of the most important analysis that should be done before the construction of an embankment dam is the seepage analysis. Inaccurate analysis of the seepage through the foundation or the dam body will lead to inaccurate design of the seepage control measures, and consequently may cause failure of the dam or high seepage losses during the operation stage. This research deals with the seepage problem in a small dam (Sotka) in Sulaimani City. Significant amount of seepage near the left abutment at the downstream toe of the dam has been noticed after first filling. A notable difference was noticed between measured and calculated values. Despite that discrepancy, seepage rate is considerably high and affects the reservoir operation efficiency. Grouting curtain is suggested as seepage control measures to reduce seepage quantity through the foundation of the dam. The estimated seepage rate after using grout curtain is reduced to 20% of the existing field seepage rate.
Keywords: Seepage; Earth Dam; Geo-Studio; Dam Foundation